Choice of reconstitution protocol modulates the aggregation state of full‐length membrane‐reconstituted synaptotagmin‐1. (22nd March 2018) - Nyenhuis, Sarah B.; Cafiso, David S.
Abstract: Synaptotagmin‐1 (Syt1) functions as the Ca 2+ sensor in neuronal exocytosis, and it is routinely incorporated into lipid bilayers along with other components of the fusion machinery in order to reconstruct the in vivo fusion process. Here, we demonstrate that the detergent used to reconstitute full‐length Syt1 has a significant effect on the state of the protein in bilayers. When octyl‐β‐d ‐glucopyranoside is used to reconstitute the protein, Syt1 is present in an aggregated state that is mediated by the long juxta‐membrane linker. EPR spectra from spin labels in the two C2 domains of Syt1 no longer resemble those obtained from a soluble construct containing these domains, and the C2B domain no longer exhibits a Ca 2+ ‐dependent membrane insertion. In contrast, when reconstituted using 3‐[(3‐cholamidopropyl) dimethylammonio]‐1‐propanesulfonate, Syt1 is largely monomeric and the EPR spectra from C2A and C2B resemble those of the soluble construct. This result demonstrates that the choice of detergent used to reconstitute Syt1 can modulate the state of the neuronal Ca 2+ ‐sensor.